2006
DOI: 10.1007/s00421-006-0265-y
|View full text |Cite
|
Sign up to set email alerts
|

Motor cortex excitability changes preceding voluntary muscle activity in simple reaction time task

Abstract: The effect of transcranial magnetic stimulation (TMS) on reaction time (RT) and motor cortex excitability in the premovement period was investigated. Single and paired-pulse TMS with 3 and 13 ms interstimulus intervals (ISI) were applied to the left motor cortex at different delays after a visual command for isometric right hand index finger abduction. Motor evoked potentials (MEPs) recorded from the right first dorsal interosseous (FDI) were analysed to assess cortex excitability. The MEPs in response to sing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
29
2

Year Published

2008
2008
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(36 citation statements)
references
References 19 publications
5
29
2
Order By: Relevance
“…The TMS pulse was delivered simultaneously with the auditory cue. Accordingly, the shorter RTs during TMS, as compared with no-TMS, trials were consistent with the results of previous studies, which have demonstrated that shorter interstimulus intervals lead to shorter RTs (Masur, Schneider, Papke, & Oberwittler, 1996;Nikolova, Pondev, Christova, Wolf, & Kossev, 2006;Pascual-Leone et al, 1992). In the present study, the facilitation effect of the single TMS pulse was approximately 40 msec, and this effect was stable across pleasant, unpleasant, and neutral images.…”
Section: Arousal Effects On Cst Excitabilitysupporting
confidence: 92%
“…The TMS pulse was delivered simultaneously with the auditory cue. Accordingly, the shorter RTs during TMS, as compared with no-TMS, trials were consistent with the results of previous studies, which have demonstrated that shorter interstimulus intervals lead to shorter RTs (Masur, Schneider, Papke, & Oberwittler, 1996;Nikolova, Pondev, Christova, Wolf, & Kossev, 2006;Pascual-Leone et al, 1992). In the present study, the facilitation effect of the single TMS pulse was approximately 40 msec, and this effect was stable across pleasant, unpleasant, and neutral images.…”
Section: Arousal Effects On Cst Excitabilitysupporting
confidence: 92%
“…Corticospinal and intracortical parameters can be assessed in the context of reaction time protocols, providing a picture of changing physiological interactions leading up to movement execution. Using single pulse TMS applied at a number of time points after a 'Go' cue (in a simple reaction time protocol), three studies have described a gradual increase in corticospinal excitability starting 80-120 ms prior to movement onset (Rossini et al 1988;Leocani et al 2000;Nikolova et al 2006). In the study of Leocani et al, this finding was accompanied by a suppression of MEPs in the contralateral resting hand (if the dominant right hand was being moved).…”
Section: Changes Affecting M1 During Movement Preparationmentioning
confidence: 99%
“…For example, reaction time was shortened when stimuli were delivered to the M1 contra at early stage of movement preparation (Leocani, et al, 2000;McMillan, et al, 2006;Michelet et al, 2010;Nikolova, et al, 2006;Soto, et al, 2010;van Elswijk, et al, 2008). However, when TMS was applied close to the expected movement onset to the M1 contra , reaction time was delayed due to disruption of movement production (Leocani, et al, 2000;McMillan, et al, 2006;Michelet, et al, 2010;Nikolova, et al, 2006;Soto, et al, 2010;Ziemann, et al, 1997).…”
Section: Reaction Timementioning
confidence: 98%
“…A large body of literature shows that corticospinal excitability for the agonist muscles of the responding hand increases only at approximately 100 ms prior to movement (Chen, et al, 1998;Evarts, 2011;Leocani, et al, 2000;Nikolova, et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation